2019
DOI: 10.1007/s10620-019-05702-7
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Controlled Attenuation Parameter in Patients with Advanced Chronic Liver Disease and Portal Hypertension

Abstract: Background Liver stiffness (LS) measured by vibration-controlled transient elastography (VCTE) is influenced by liver fibrosis and hepatic perfusion pressure. VCTE-based controlled attenuation parameter (CAP) is a noninvasive marker for hepatic steatosis (HS). Aims To investigate the diagnostic performance of CAP in patients with advanced chronic liver disease (ACLD)/portal hypertension (PHT: hepatic venous pressure gradient (HVPG) ≥ 6 mmHg). Methods Eighty-eight patients with LS ≥ 10 kPa and/or HVPG ≥ 6 mmHg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Therefore, CAP needs to be interpreted with caution in these patients. Apart from diabetes and BMI, liver fibrosis has been suggested as a factor influencing CAP values 13 , 30 , 31 . However, reports on its impact are inconsistent, but could have attenuated the correlation of CAP and histology in our cohort.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Therefore, CAP needs to be interpreted with caution in these patients. Apart from diabetes and BMI, liver fibrosis has been suggested as a factor influencing CAP values 13 , 30 , 31 . However, reports on its impact are inconsistent, but could have attenuated the correlation of CAP and histology in our cohort.…”
Section: Discussionmentioning
confidence: 73%
“…Apart from diabetes and BMI, liver fibrosis has been suggested as a factor influencing CAP values. 13,30,31 However, reports on its impact are inconsistent, but could have attenuated the correlation of CAP and histology in our cohort. Of note, inflammation (as assessed serologically) does not significantly impact on the performance of CAP, 13 which has been confirmed by our study.…”
Section: Discussionmentioning
confidence: 74%
“…Interestingly, genetic variants did not influence liver disease regression in our study, although we observed a trend towards a discordancy in the evolution of CAP between carriers and non-carriers of the PNPLA3 rs738409 G -allele (i.e., decreases in non-carriers vs. increases in carriers). Nevertheless, the diagnostic ability of CAP in patients with ACLD is limited [ 51 ], and the impact of genetic variants on long-term outcomes has yet to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the reliability of CAP may be lower in patients with CSPH. 17 Moreover, in this cohort, no histologic confirmation of fibrosis at the time of LSM assessment was available, as such we did not have access to the gold standard to confirm the diagnosis of cACLD. According to Petta et al, 18 higher CAP values reduce LSM accuracy for fibrosis using the M probe; despite our study being performed in patients who were assessed using the XL probe, we cannot rule out that some of the patients with high CAP values classified as cACLD based on a LSM of 10 kPa or greater might have a milder stage of fibrosis in which liver-related events are not expected.…”
Section: Discussionmentioning
confidence: 99%